Pengaruh Penerapan Konsep Value for Money dan Sistem Pengendalian Internal Pemerintah terhadap Akuntabilitas Publik di Kota Padang - Josse Andre Warsito; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2023)
This study's goal was to investigate the impact of applying the idea of value for money and the internal control structure of the government to regional organizations' public accountability in the city of Padang. All 43 regional groups in the city of Padang participated in this study. Total sampling was the chosen sampling strategy. The information used is primary information that was obtained from interviews and circulated questionnaires. Analysis is conducted using multiple linear regression. The use of the value for money idea has had a considerable and partially favorable impact on the public accountability of regional organizations in the city of Padang, according to the study's findings. While the government internal control system partially has a negative and insignificant effect on public accountability of regional organizations in the city of Padang.